2022
DOI: 10.3389/fmars.2022.861932
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Net Ecosystem Productivity (NEP) of Seaweed Farms

Abstract: The important role of vegetated ecosystems in the sequestration of carbon has gained strong interest across a wide variety of disciplines. With evidence growing of the potential for macroalgae ecosystems to capture carbon, there is burgeoning interest in applying newfound knowledge of carbon capture rates to better understand the potential for carbon sequestration. Seaweed farms are expected to play a significant role in carbon capture; advocates for the expansion of seaweed farms are increasing in many countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…This is necessary because the margin between kelp farms serving as nutrient sinks versus nutrient sources is thin. In a study monitoring carbon flux in three Japanese kelp farms [36], results as to whether a kelp farm is a sink or source for carbon were mixed and suggested that it depends on how long the condition of site allows the kelp to live in an autotrophic versus heterotrophic state. In our study, the low-nitrogen condition of the sites likely shortens the time in which those farms serve as sinks, and we propose that the high-nitrogen demand of A. marginata can further shorten that window.…”
Section: Discussionmentioning
confidence: 99%
“…This is necessary because the margin between kelp farms serving as nutrient sinks versus nutrient sources is thin. In a study monitoring carbon flux in three Japanese kelp farms [36], results as to whether a kelp farm is a sink or source for carbon were mixed and suggested that it depends on how long the condition of site allows the kelp to live in an autotrophic versus heterotrophic state. In our study, the low-nitrogen condition of the sites likely shortens the time in which those farms serve as sinks, and we propose that the high-nitrogen demand of A. marginata can further shorten that window.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, seaweeds including macroalgae have become a global focus, particularly because of their inclusion within coastal plant communities (Duarte et al 2013) and the role they play in marine carbon storage and sequestration (Krause-Jensen and Duarte 2016). Seaweeds store and increase coastal carbon capacity (Sato et al 2022), adding to the coastal assimilation of carbon (Muraoka 2004;Sondak et al 2017;Ould and Caldwell 2022). Due to their e ciency as primary producers (Mann 1973; Pessarrodona et al 2022), seaweed carbon assimilation accounts for 70% of coastal assimilation despite the relatively small global area of coastal habitats (Nellemann et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Large brown macroalgae, including kelp (Order Laminariales) and fucoids (Order Fucales), are dominant taxa in subpolar and temperate reef ecosystems and are known to be highly productive (Steneck et al, 2002). Moreover, increasing evidence suggests their potential for use in carbon sequestration and therefore contribution to mitigating climate change (Fillbee-Dexter and Wernberg, 2020;Watanabe et al, 2020;Sato et al, 2022). However, regional kelp forests dominated by perennial species are declining under ocean warming in temperate areas (Smale, 2020).…”
Section: Introductionmentioning
confidence: 99%